Raman Spectroscopy Study of Ancient Vaccaei (s. IV-I BC) Glass Beads found at the Necropolis of "Las Ruedas" (Padilla de Duero, Valladolid, Spain). Issue 1 (1st April 2022) - Pinto, Javier; Barroso-Solares, Suset; Souto, Jorge; Rodriguez, E.; Sanz-Minguez, Carlos; Prieto, Angel Carmelo
Abstract: Glass pieces were highly appreciated imported goods in the Protohistory of the Iberian Peninsula. Therefore, these remainings could provide evidence about the commercial or political relationships among contemporary cultures. However, archaeometry studies of glass beads are scarce in the Iberian Peninsula, and their results are difficult to generalize, as the studied glass beads are often found without clear historical context. On the contrary, the archaeological site of Pintia (Padilla de Duero, Valladolid, Spain) have provided about one thousand glass beads in the last decades, being a significant percentage found in well-contextualized closed tombs. Ten representative samples found in closed tombs have been selected in this work to deepen in our knowledge of the Vaccaei culture (IV-I BC). The study of the glass network of these pieces by Raman spectroscopy provided an estimation of the firing temperatures employed to produce such samples, and hence evidenced the technological development required for their production. Also, the combination of the Raman spectroscopy results with elemental analysis by ESEM/EDX narrowed the composition of the glass, as well as the pigments employed to obtain blue, yellow-orange, and green tones. Particularly, the presence of complex pigments such as lead antimoniates (e.g., Naples yellow) was confirmed. Moreover, it was possible to identify the surface degradation processes suffered by these samples. Finally, information about the complex funerary rituals performed by the Vaccaei, involving cremation, was also provided. The evolution of the glass network of glass beads altered by the cremation, evidenced by Raman spectroscopy, narrow the cremation temperature to about 600 °C.